The Possibility of Estimating the Length of Humerus and Femur on the Ground of the Measurments of the Parts of Shoulder and Hip Joints. - Kozłowski, Wiesław (Anthropological Review, 1992)
The possibility of estimating the length of humerus and femur on the ground of the measurments of the parts of shoulder and hip joints. The regression equation was given to help to reconstruct the length of the bone taken from the fragmented sekeleton.